Equivalent Modulus and Mass Loss of C/C-SiC Gradient Matrix Composites at High Temperature. Issue 1 (1st April 2022) - Li, Zhaoyi; Liang, Wei; Liu, Yufeng
Abstract: The oxidation at high temperature of carbon fiber reinforced carbon-silicon carbide (C/C-SiC) gradient matrix composites results in structural damages and performance degradation. Oxidation kinetics model of C/C-SiC gradient matrix composites was built. A representative volume element (RVE) was established according to the microstructure of the composites. The evolution law of the structure characterization of the composites and the mass loss model were derived from the oxidation kinetics model. And equivalent elastic modulus with oxidation time at different temperatures and coefficient of thermal expansion(CTE) at different temperatures were calculated by RVE. The results show that the equivalent elastic modulus decreases with oxidation time and increases rapidly after the crack heals. The higher the temperature, the lower decreasing rate. And the equivalent CTE increases with temperature, while the increasing rate decreases with temperature. The calculated result of mass loss is consistent with the previous research.